Terminology Management as a Complement of the Translator Training Process within a Philological Study - Plęs, Łukasz M. (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
The present chapter is an attempt to discuss the issue of terminology management as a part of the translator training process within a philological study as well as the methods of its implementing. The course of terminology management discussed in the paper consists of a theoretical and a practical module. The second one includes three steps: terminology work sensu stricto, terminology management and integrating of termbases being prepared or made available in the process of translation with the aid of the CAT tools. The practical work was based on small and medium-sized terminology projects carried out by university students.